Kościół nauczający i poszukujący. Na marginesie eklezjologii Francisa A. Sullivana - Dawidowski, Wiesław (Śląskie Studia Historyczno-Teologiczne, 2005)
The 20th century may be called the age of debate over magisterium. One of the main figures and experts in this debate is an American theologian F. A. Sullivan. His works including Magisterium: Teaching Authority in the Catholic Church, New York 1983; The Church We Believe In: One, Holy, Catholic and Apostolic, New York 1988, and Creative Fidelity. Weighing and Interpreting Documents of the Magisterium, Dublin 1996 are considered classics in contemporary ecclesiology. This article presents Sullivan’s views on the issues of infallibility, ordinary magisterium, and the question of subsistit. The American theologian bases his approach on the historical-critical method and on fidelity of the teaching of Vaticanum II. Like most of the contemporary theologians, Sullivan does not believe in a systematic theology. His ecclesiology is deeply ecumenical and seeks to build bridges between the Church as known in the profession of faith, and the Church of our everyday experience.